(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
The study was aimed to describe two wild phenotypes, where exist as scattered groups of shrubs in villages (Ras auj, Slayeb al-Bahaouliah, Al-Rasteen), Lattakia governorate. This study was carried out during the years 2013 – 2014 . first phenotype has a bluish black fruits, gave symbol A. Second phenotype with spherical and white fruits, gave symbol B. phenotype (B) was exceeded in average of shrub height opposite to phenotype (A) , where recorded in mean (2.7 – 2.3 m) respectively, as well as it was exceeded in the length ,width, leaf area ,in addition to weight , length , and width of the fruit and its size , fruit size for A and B phenotypes gave in mean (0.801,1.032 cm3) respectively. While the symbol A was exceeded on symbol B in the average number of main branches (six branches on A, three branches on B). Thick leaf for phenotypes A and B were (0.019, 0.024 cm) respectively, whereas no differences between two phenotypes in the average number of branching angle where was recorded approximately (79°). The date of the beginning of the flowering of the two phenotypes, was between (9-16) June and the number of stamens in the flower was big which recorded between (125, 150) stamen in both phenotypes. دراسة أولية لتوصيف طرازين بريين من نبات الريحان (الآس الشائع) Myrtus communis L. المنتشر في بعض المواقع شمال محافظة اللاذقية هدفت هذه الدراسة إلى توصيف طرازين بريين منتشرين بشكل تجمعات مبعثرة في قرى (رأس عوج ، صليب البهلولية ، الرستين) التابعة لمنطقة اللاذقية- ناحية البهلولية ، وتمت هذه الدراسة خلال عامي 2013- 2014 . أعطي الرمز ((A للطراز الأول ذو الثمار السوداء المزرقة ، وأعطي الرمز ((B للطراز الثاني ذو الثمار الكروية البيضاء . بينت الدراسة تفوق الطراز (B) على الطراز((A في متوسط ارتفاع الشجيرة حيث سجلت (2.7 – 2.3 م) على التوالي، وكذلك تفوق في متوسطات طول وعرض ومساحة الورقة إضافةً إلى متوسط وزن وطول وعرض الثمرة وحجمها إذ كان حجم الثمرة للطرازين A، B على التوالي (0.801، 1.032) سم3 على التوالي ، بينما تفوق الطراز ((A على الطراز ((B بعدد الفروع الهيكلية على الساق الرئيسة ( 6 فروع هيكلية للطراز A ، 3 فروع هيكلية للطراز B) ، كانت متوسط سماكة الورقة للطرازين A و B ( 0.019، 0.024 سم) على التوالي ، بينما لم يكن هناك أي اختلاف بين الطرازين في زاوية التفرع حيث سجلت تقريباً (80º )، كان تاريخ بدء الإزهار للطرازين بين (9-16) حزيران ، و كان عدد الأسدية في الزهرة كبير في كلا الطرازين حيث سجل مابين (120-150) سداة.